Case Report: Adult UESL mimicking a simple hepatic cyst and initially misdiagnosed as a benign lesion - Mo, Yuanhang; Feng, Jinrong; Liang, Chunhui; Ma, Xiaoqing; Wu, Zongquan; Su, Xingwang; He, Shan; Xu, Xiaoyou; Liao, Yongfeng; Liu, Yongdong (Frontiers in Oncology, 2025)
We report a case of undifferentiated embryonal sarcoma of the liver (UESL) in a 50-year-old woman with no prior history of liver disease. The patient presented with abdominal distension; physical examination revealed only mild tenderness, and routine laboratory tests were within normal limits. Abdominal ultrasound and computed tomography (CT) both identified a cystic mass located in the right lobe of the liver. Initially, the patient underwent fenestration and drainage of a suspected hepatic cyst, and the histopathological analysis was consistent with a benign hepatic cyst. However, the patient was readmitted due to tumor recurrence, and a liver tumor resection was subsequently performed. The final pathological diagnosis was confirmed as UESL. Following surgery, the patient received adjuvant chemotherapy. Unfortunately, the patient passed away, with an overall survival time of 9 months. This case also provides clinicians with a profound lesson. In the face of large lesions, even when imaging suggests benign cysts, greater vigilance should be maintained regarding the possibility of malignant pathology. Every effort should be made to complete comprehensive preoperative evaluations to establish a clear diagnosis, along with meticulous perioperative planning and systematic postoperative follow-up, in order to minimize the risk of missed or delayed diagnosis.